Proposta didática para o ensino de solo na disciplina geografia - Botelho, Juvenal Severino (2017)
This dissertation presents the investigative studies done in the elaboration of a didactic proposal for the teaching of soil in the geography discipline, based on Geosystemic Theory. The subjects of the research were 40 students of the 1st year of the Integrated Technical Level Courses in Chemistry and Mechanics and 2 teachers of the effective staff all of the IFAMCMC. The research is of the qualitative type and it was developed from the accomplishment of intervention activities characterized by dialogic expositive classes and practical activities in the field and laboratory experiments. The instruments of data collection used were the questionnaires, the guiding scripts and the evaluations performed in each activity. The research was guided primarily by a bibliographical survey for the contextualization and theoretical basis regarding the researched topic, as well as a documentary analysis with focus on the textbook used. The dialogic expository classes empowered students to perform practical activities. Field classes were held in the South and East regions of the city of Manaus, where Industrial Districts I and II are located respectively. The experiments were developed in the Microscopy laboratory, in the premises of the IFAM-CMC. The analysis of the didactic book, allowed to realize that there is emphasis on the geological and agronomic conception; The approach on soil formation presents concepts such as weathering, pedogenesis and soil, without a clear explanation among them; It does not differentiate between shallow and deep soils; The updated classification of soil classes according to SiBCS (Brazilian Soil Classification System) is not used; Characterizes the Purple Land as synonymous with latosol; The pedogenetic processes are cited unrelated to the soil formation factors and the leaching is conceptualized in the wrong way. In the field, the students realized that there is a relationship between rock, soil and weathering. The laboratory experiments were satisfactory, since the students were able to identify the youngest horizon (O) and the oldest horizon (R) of the soil, to texture and to differentiate the granulometric fractions by size and texture of the soil, understood the colors of the soils and also the capacity of infiltration and water retention in soils with different characteristics. In relation to the teachers, it was found that they regularly plan their classes, use numerous didactic resources, criteria and evaluation instruments and emphasizing that practical activities are important for meaningful learning of soil content and erosion. Intervention activities provided improvement of the teaching-learning process and environmental awareness of students. The Didactic Guide entitled ORIGIN, FORMATION AND EROSION OF THE SOIL: a proposal for the teaching-learning process was positively assessed by all the research subjects and integrates of this dissertation.